COMMUNICATION OF TEACHERS AND DEAF STUDENTS IN INTRODUCING SIGN LANGUAGE IN THE EXTRAORDINARY SCHOOL PERTIWI PONOROGO - Agustina, Dwi Aziz Azizah; Prabowo, Galih Akbar (QAULAN: Journal of Islamic Communication, 2021)
Deafness is a disorder that occurs in the human sense of hearing. Loss of hearing function causes deaf people unable to hear and communicate verbally so that they experience delays in language development. Sign language is used by deaf people as a communication language. Sign language needs to be introduced by teachers of SLB Pertiwi Ponorogo to students with hearing impairments in order to get an agreement on the meaning of the signs used during communication. This research uses a descriptive type of research with a qualitative approach. The results of this study indicate the following: first, the communication carried out by the teacher in introducing sign language uses total communication by means of oral, written, pictures, signs, spelling, and lip-reading. Second, students gave a positive response indicated by a change in attitude following the cues displayed by the teacher. Students give negative responses indicated by emotional changes such as expressions of anger, confusion, silence, and even rejection from students. Third, the communication position in this study lies in the communicator, message, and communicant, namely the communication process barriers, physical barriers, and semantic barriers.